87.8k views
2 votes
Simplify 8^-5 over 8^-3

2 Answers

0 votes


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \cfrac{8^(-5)}{8^(-3)}\implies \cfrac{1}{8^(-3)\cdot 8^5}\implies \cfrac{1}{8^(-3+5)}\implies \cfrac{1}{8^2}\implies \cfrac{1}{64}

User Thomas Enebo
by
5.6k points
3 votes

Answer:

64-5 divided by 64-3 is 59 divided by 61. 59

8 squared is equal to 64. -----

61

Explanation:

User Keithamus
by
6.1k points